EFFICACY OF DIODE LASSER 405 NM WITH CHLOROPHYLLS AS PHOTOSENSITIZER ON Enterococcus faecalis - Sri Kunarti; Amellia Tjandra; Edhie Arif Prasetyo (Conservative Dentistry Journal, 2018)
Background: The presence of persistent infections in the root canals by microorganisms causes root canal failure. The most commonly found bacteria that cause persistent infection is Enterococcus faecalis. PDI / photodynamic inactivation is an in vitro approach to inactivation of microorganisms. The combination of light and photosensitivity of chlorophyll in PDI will cause photoinactivation in bacteria. Long radiation of PDT can affect the production of singlet oxygen and ROS (Reactive Oxygen Species) to kill Enterococcus faecalis bacteria. Objective: To prove the effect of 405 nm laser diode  with and without chlorophyll photosensitizer and the irradiation effect of 405 nm laser diode on the number of CFU of Enterococcus faecalis bacteria. Method: This study used the Enterococcus faecalis bacteria cultur  which was divided into 5 groups. Group I as control group, Group II irradiation 30 ', III chlorophyll + irradiation 30', IV irradiation 60 ', V chlorophyll + irradiation 60'. After incubation, the bacteria count was calculated with Quebec Colony Counter and analyzed by Shapiro-Wilk test, Levene test and Anova test. Results: There were significant differences (p <0.05) between the number of colonies of Enterococcus faecalis bacteria in each treatment group. Longer duration of PDT exposure (Group II and IV) with chlorophyll showed less number of Enterococcus faecalis bacteria. Conclusion: The longer the PDT irradiation, the less number of Enterococcus faecalis bacteria. The 60-second radiation with chlorophyll showed the least amount of Enterococcus faecalis bacteria.